Knowledge and Practice of Personal Hygiene Among the High School Students in A Rural Area of Mymensingh, Bangladesh - Begum, Maksuda; Alam, Fakir Sameul; Hossain, Md Tufael; Hasan, AHM (Community Based Medical Journal, 2022)
This cross-sectional descriptive study was conducted during November 2019 to assess knowledge and practice of personal hygiene among the high school students in a rural area of Mymensingh. Proper knowledge and practice of personal hygiene plays critical role in avoiding communicable diseases and benefit the high school students to enjoy healthy life with excellent academic career. Respondents were 244 high school students of different schools in Churkhai, Bhavokhali, Mymensingh who were selected purposively. Age ranged from 10 years to 17 years, mean age 13.32 years with SD ± 1.505 years; boys predominant (boy: girl ratio 146.5: 100). Data were collected on a predesigned questionnaire by direct interviewing the students. Knowledge and practice of personal hygiene were measured using scoring based on correct answers. Data analysis was done by SPSS version 20.0. Most of them (217) 88.93% were apparently healthy. Based on presenting symptoms and signs the diagnosed illnesses were ARI (7) 2.87%, diarrhea (5) 2.05%, head lice (5) 2.05%, scabies (4) 1.64%, injury (3) 1.23%, dental caries (2) 0.82% and peptic ulcer disease (1) 0.41%. Important personal hygiene practices inquired were frequency of regular bathing with use of soap or shampoo, combing hair, brushing teeth, hand washing, trimming nails, wearing shoes, clean clothes, avoidance of smoking and appropriate allocation of time for study, outdoor, indoor activities, rest and sleep. Based on aggregate items 80.74% had excellent knowledge and practice on personal hygiene and 19.26% had good knowledge and practice. Knowledge and practice were concordant in all elements inquired except smoking. Knowledge about harm of smoking was 100.00% though avoidance of smoking was 97.95%. Knowledge and practice scores were influenced by educational grade (class VIII at peak), literate parents, better socioeconomic condition and absence of illness. The results are better than the findings of studies conducted in our country and neighboring countries. CBMJ 2022 July: vol. 11 no. 02 P: 136-143